Deep-Saddle-Shaped Nanographene Induced by Four Heptagons: Efficient Synthesis and Properties - Borrisov, Boris; Beneventi, Giovanni Mariano; Fu, Yubin; Qiu, Zhen Lin; Komber, Hartmut; Deng, Qing Song; Greißel, Phillip; Cadranel, Alejandro; Guldi, Dirk Michael; Ma, Ji; Feng, Xinliang (Journal of the American Chemical Society, 2024)
The construction of multiple heptagonal rings in nanographene is the key step for obtaining exotic carbon nanostructures with a negative curvature and intriguing properties. Herein, a novel saddle-shaped nanographene (1) with four embedded heptagons is synthesized via a highly efficient one-shot Scholl reaction from a predesigned oligophenylene precursor. Notably, a quadruple [6]helicene intermediate was also obtained and isolated by controlling the Scholl reaction conditions. Interestingly, the single crystal structures of 1 display a saddle geometry induced by the four embedded heptagons, resulting in a deep curvature with a width of 16.5 Å and a depth of 8.0 Å. Theoretical calculations at the molecular level suggest a weak antiaromatic character of the heptagons in 1. Remarkably, compound 1 exhibits dual fluorescence from S1 and S2. The deep-saddle-shaped geometry in 1 defines host-guest interactions with fullerenes, which were explored in titration experiments and by theoretical methods. The resulting 1@C60 are stable and are subject to an electron transfer from photoexcited 1 to C60. Our current study underscores the influence of heptagon rings on the photophysical, self-assembly, and electron-donating properties of NGs.
CRIS-Team Scopus Importer:2024-10-18